Using of Game-based learning via Facebook Live to Enhance Distance Learning in the Time of COVID-19 Pandemic - Nisakorn Saengprachum (SEAQIS Journal of Science Education, 2021)
The use of current and emerging platforms in education is becoming an intriguing topic among educators and educational institutions. Using live-stream media like Facebook lives can provide a more intimate level of engagement with audiences. Besides, the use of games in education plays a vital role in engaging students by encouraging a hands-on approach. This study aimed to investigate implementing a game-like via Facebook live feature as a supportive science learning tool. This study examined how Thai secondary school teachers and students performed and interacted with five live-streaming activities. In each live-stream activity, the participants needed to answer ten questions in the scheduled time. The resource used for posing questions is secondary school science materials related to the Thai Basic Education Core Curriculum's learning standard. The participants were required to join the live-stream video as well as answer ten questions in real-time. All participants were provided materials uploaded on the Facebook wall two days before the live-streaming day. The result of this study showed that the number of participants who scored more than the given criteria had steadily increased, suggesting that the Facebook live feature is a useful tool for learner engagement. It indicates that the Facebook live feature increases students' motivation and attention since it can enhance visual skills, improve students' interaction and collaboration abilities with their peers.